The clinical features of amyotrophic lateral sclerosis: diagnosis, natural history and epidemiology - Talbot, Kevin (Henry Stewart Talks, 2016)
Onset & clinical features, Differential diagnosis, Investigation of a suspected case of ALS, Clinical diagnosis, Regional syndromes, Survival & progression, Age distribution & life expectancy, Familial ALS, Frontotemporal dementia, Cognitive & emotional impairment in ALS